Investigation of Hungarian Conquest Period (10th c. AD) archery on the basis of activity-induced stress markers on the skeleton - preliminary results - Tihanyi, Balázs; Bereczki, Zsolt; Molnár, Erika; Berthon, William; Révész, László; Dutour, Olivier; Pálfi, György (Acta Biologica Szegediensis, 2015)
In this paper we introduce the preliminary results of an anthropological investigation of archery-induced stress markers on the skeletons of a Hungarian Conquest Period cemetery. According to historical and archaeological data the bow was a common weapon in this era. Our main question is whether anthropological data also reflect this fact, or not. We focused on entheseal changes that occur on the skeleton as a result of physical stress. Macroscopic analysis was performed of the scapulas, claviculas, humeruses, radiuses and ulnas of the “archer” graves and the unarmed adult male graves. We found hypertrophy at the attachment of a wide scale of muscles of the upper body and a few of them - such as m. deltoideus, m. pectoralis major, m. latissimus dorsi, m. brachialis and m. biceps brachii - appear in high frequency. As a preliminary result we can state that the anthropological and archaeological data do support each other concerning the application of archery in the population in question.